The Process of Personality Changing of Jess in Ficarra’s Focus (2015) - Anis Hidayah (Metaphor, 2021)
This research is conducted to analyze the process of personality changing of Jess in Ficarra's Focus (2015) movie. There are two problem statements that the researcher used in this research. (1) How is the personality of Jess reflected in Ficarra’s Focus?. (2) How is the process of personality changing of Jess in Ficarra’s Focus ?. The researcher uses qualitative method in this research. The data source is the movie of Ficcara’s FOCUS (2015) and the source of data is the script of movie.The method of collecting data in this research includes reading, identifying, classifying, and selecting. The method of analysing the data are done by displaying, explaining, and interpreting. The theory and approach that the researcher used is the psychology of literature based on Alfred Adler Theory. As a result of this research, first Jess has a smart calmness and obedient personality, she also learns from the mistakes. Second, the process of personality changing is based on Alfred Adler individual theory. Jess changes to become superior and knows the purpose in her life.